PERSEPSI WISATAWAN TERHADAP OBJEK WISATA ALAM LEMBAH CILENGKRANG TAMAN NASIONAL GUNUNG CIREMAI - , DINAR ADITYA RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ciremai Mountain National Park has a high potential of natural resources as a nature tourism destination. One of them is Lembah Cilengkrang Natural Tourism Object that offers a natural atmosphere of the mountains with the main attraction is Sawer waterfall and natural hot water submerged pool. Great potential not accompanied with high visits, in the last year the number of tourists are decreased which can be caused by the perception of tourists. The purpose of this research are (1) to know the profile of tourists in nature tourism object Cilengkrang Valley, (2) to determine the perception of tourists in nature tourism object Cilengkrang Valley and (3) to determine the relationship between the profile of tourists with perception of tourists in nature tourism object Cilengkrang Valley. This research was conducted in August 2013 with survey method. Data collected by collection of secondary data from managers, direct observations, interviews, and distribution of questionnaires to tourists. The sampling method was used simple random sampling. The analysis was used to measure the touristsâs profile is a quantitative descriptive analysis, to determine the tourists's perception was used scoring analysis, and to know the profile associated with the perception of tourists using chi square analysis. Research results show that the Object Nature Valley Cilengkrang tourist have a profile that is: sex tourist men with a percentage of 68 % , which is high school education with a final percentage 41 % , 20-30 year age group was 61% , comes from Kuningan valley Cilengkrang 71.54 value that is based on the analysis of the scoring included into the category quite well. In general there is no relationship between the perception of tourists with their profile only to travelers who have a job profile relationship with perceptions of service in the Object Nature Valley Cilengkrang .